Cerebral venous sinus thrombosis-related epileptic seizures and their clinical features (Annals of Medical Research, 2021)
Aim: Cerebral venous sinus thrombosis (CVST) is a severe neurological disease that may cause disability and death. Its clinical symptoms are varied. Epileptic seizures may manifest as early signs of the disease in 30-40% of patients. We aim to compare patients presenting with seizures with those presenting without seizures in CVST patients.
Keywords: Cerebral Venous Sinus Thrombosis; Seizure; Epilepsy.